A NEW MATHEMATICAL MODEL FOR THE CUTTING STOCK/LEFTOVER PROBLEM - Arenales, Marcos Nereu; Cherri, Adriana Cristina; Nascimento, Douglas N. Do; Vianna, Andréa (Sociedade Brasileira de Pesquisa Operacional, 2015)
ABSTRACT This paper addresses the cutting stock/leftover problem (CSLP), which differs from the ordinary cutting stock problem (CSP) by retaining stock leftovers that can be cut in the future to meet new demands. Therefore, leftovers are not considered waste in the current period. A new mathematical model for the CSLP is presented to capture a well-used strategy in the practice of cutting, which consists of partially cutting the objects in stock, and keeping the leftovers to be cut in the next periods. Computational experiments were made for the one-dimensional case, although other dimensions can be considered straightforward.
Keywords: cutting stock problem; usable leftovers; mathematical model; column generation